Uniaxially stretched polyethylene composite film material as well as preparation method and application thereof
Through multiple modification strategies, the performance of montmorillonite and metallocene polyethylene is optimized, and the problem of insufficient gas barrier performance of traditional polyethylene films is solved, and efficient barrier, mechanical performance improvement and processing performance improvement of composite materials is achieved.
Patent Information
- Application Number
- CN202510368636.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
Traditional polyethylene films perform poorly in gas barrier properties, especially in their barrier capabilities to oxygen and water vapor, which limits their application in high-end packaging materials.
The performance of montmorillonite and metallocene polyethylene is synergistically optimized through multiple modification strategies, including ultrasonic peeling, 3-aminopropyltriethoxysilane surface modification, N,N-dimethyloctadecyl ammonium chloride intercalation modification, zinc oxide imparting antibacterial and ultraviolet shielding functions, and maleic anhydride grafting and glycidyl methacrylate synergistic modification, to improve the dispersion, interface compatibility and interlayer stability of montmorillonite.
It significantly improves the barrier properties, mechanical properties and processing properties of composite materials, and meets the application needs of high-performance films.
Smart Images

Figure CN119875177A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of film materials and relates to a uniaxially stretched polyethylene composite film material and a preparation method and application thereof. Background Art
[0002] Polyethylene is a thermoplastic with excellent mechanical properties and chemical stability. Due to its excellent physical properties, it is widely used in many fields, including packaging, construction and automobiles. In the packaging industry, polyethylene film is favored because of its lightness, durability and economy, and can effectively meet the various needs in daily life and industrial production. However, despite the good physical properties of polyethylene, traditional polyethylene film performs relatively poorly in gas barrier properties, especially in the barrier capacity against oxygen and water vapor. This defect limits its application in high-end packaging materials, especially in the fields of food, medicine, etc., which have strict requirements on moisture and oxygen resistance.
[0003] In order to improve the gas barrier properties of polyethylene films, researchers have introduced nanomaterials into the polyethylene matrix in order to achieve performance improvements. Among them, montmorillonite, as a widely studied nanomaterial, has shown good modification potential due to its high specific surface area, layered structure and excellent chemical stability. Researchers hope to significantly improve the barrier properties of polyethylene films by combining montmorillonite as a modifier with polyethylene, thereby broadening its application range.
[0004] However, simply introducing montmorillonite into polyethylene is not enough to ensure its effective dispersion in the polymer matrix. Traditional montmorillonite modification methods often result in insufficient dispersion in the polymer matrix, which not only affects the performance of montmorillonite, but may also cause the gas barrier and mechanical properties of polyethylene films to fail to achieve the expected results. When montmorillonite particles cannot be evenly dispersed in polyethylene, aggregates may form inside the material, which not only weakens the barrier effect of the material, but may also lead to a decrease in mechanical properties, affecting the durability and stability of the material. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a uniaxially stretched polyethylene composite film material and its preparation method and application. The present invention synergistically optimizes the performance of montmorillonite and metallocene polyethylene through multiple modification strategies, significantly improving the comprehensive properties of the composite material. The dispersibility, interfacial compatibility and interlayer stability of montmorillonite are improved by ultrasonic stripping, 3-aminopropyltriethoxysilane surface modification and N, N-dimethyloctadecyl ammonium chloride intercalation modification, while zinc oxide is introduced to impart antibacterial and ultraviolet shielding functions; maleic anhydride grafting further enhances the interfacial bonding force. Metallocene polyethylene is modified by synergistic grafting of maleic anhydride and glycidyl methacrylate, and polar groups are introduced to enhance the interfacial compatibility with polar nanomaterials, and to improve flexibility and processing performance. Magnesium chloride promotes grafting efficiency, tributyl phosphate improves dispersibility and fluidity, and enables the modified metallocene polyethylene and montmorillonite to be evenly distributed, ultimately greatly improving the barrier properties, mechanical properties and processing properties of the composite material to meet the application requirements of high-performance films.
[0006] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a uniaxially stretched polyethylene composite film material, the method for preparing a uniaxially stretched polyethylene composite film material comprising: S1: ultrasonically treating a montmorillonite dispersion to obtain an exfoliated montmorillonite dispersion, and adding 3-aminopropyltriethoxysilane to obtain a pretreated montmorillonite; S2: reacting the pretreated montmorillonite with N,N-dimethyloctadecylammonium chloride and zinc oxide to obtain ion coordination / intercalation modified montmorillonite; reacting the pretreated montmorillonite with maleic anhydride and diisopropylbenzene peroxide in toluene to obtain polar group grafted nanosheet powder; S3: melt-blending metallocene polyethylene with maleic anhydride, dicumyl peroxide and antioxidant to obtain a preliminarily grafted metallocene polyethylene; blending the preliminarily grafted metallocene polyethylene with glycidyl methacrylate, ethyl acrylate, magnesium chloride and tributyl phosphate to obtain a modified polyethylene compatibilizer; S4: The polyethylene resin, the polar group-grafted nanosheet powder, the modified polyethylene compatibilizer and the additive are melt-processed and treated to obtain a uniaxially stretched polyethylene composite film material.
[0007] Specifically, S1: exfoliating a montmorillonite dispersion by ultrasonic treatment to obtain an exfoliated montmorillonite dispersion, adding 3-aminopropyltriethoxysilane to obtain a reaction solution A, stirring the reaction, centrifuging, washing, and drying to obtain a pretreated montmorillonite; S2: Add N,N-dimethyloctadecylammonium chloride and zinc oxide to the pretreated montmorillonite dispersion to obtain a reaction solution B, stir and react, and then spray dry to obtain an ion-coordinated / intercalated modified montmorillonite; disperse maleic anhydride in toluene, add diisopropylbenzene peroxide and mix to obtain a grafting solution, add the ion-coordinated / intercalated modified montmorillonite under an inert atmosphere to obtain a reaction solution C, react at a constant temperature, then heat and react, and rotary evaporate to obtain a polar group-grafted nanosheet powder; S3: melt-blending metallocene polyethylene with maleic anhydride, diisopropylbenzene peroxide and antioxidant, and extruding to obtain preliminary grafted metallocene polyethylene; and blending and extruding the metallocene polyethylene with glycidyl methacrylate, ethyl acrylate, magnesium chloride and tributyl phosphate to obtain a modified polyethylene compatibilizer; S4: The polyethylene resin is mixed evenly with the polar group grafted nanosheet powder, the modified polyethylene compatibilizer, the antioxidant and the lubricant, and then put into a twin-screw extruder to extrude and cast into a sheet, which is then uniaxially stretched, heat-set and then cooled to obtain a uniaxially stretched polyethylene composite film material.
[0008] As a preferred technical solution of the present invention, in step S1, the mass fraction of the montmorillonite dispersion is 5-10wt.%, for example, it can be 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5% or 10.0%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0009] In some optional embodiments, the power of the ultrasonic treatment of the montmorillonite dispersion is 200-300 W, for example, it can be 200 W, 210 W, 220 W, 230 W, 240 W, 250 W, 260 W, 270 W, 280 W, 290 W or 300 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0010] In some optional embodiments, the ultrasonic treatment time of the montmorillonite dispersion is 30-60 min, for example, it can be 30 min, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0011] In some optional embodiments, the mass ratio of 3-aminopropyltriethoxysilane to montmorillonite is 0.03-0.05:1, for example, it can be 0.030:1, 0.032:1, 0.034:1, 0.036:1, 0.038:1, 0.040:1, 0.042:1, 0.044:1 or 0.050:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0012] In some optional embodiments, the stirring reaction temperature of the reaction liquid A is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] In some optional embodiments, the stirring reaction time of the reaction liquid A is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] As a preferred technical solution of the present invention, in step S2, the mass fraction of the pretreated montmorillonite dispersion is 2-4wt.%, for example, it can be 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8% or 4.0%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] In some optional embodiments, the mass ratio of N,N-dimethyloctadecylammonium chloride to pretreated montmorillonite is 0.02-0.05:1, for example, it can be 0.020:1, 0.022:1, 0.024:1, 0.026:1, 0.028:1, 0.030:1, 0.032:1, 0.034:1, 0.036:1, 0.038:1, 0.040:1, 0.042:1, 0.044:1 or 0.050:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In some optional embodiments, the mass ratio of zinc oxide to pretreated montmorillonite is 0.01-0.03:1, for example, it can be 0.010:1, 0.012:1, 0.014:1, 0.016:1, 0.018:1, 0.020:1, 0.022:1, 0.024:1, 0.026:1, 0.028:1 or 0.030:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In some optional embodiments, the stirring reaction temperature of the reaction liquid B is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In some optional embodiments, the stirring reaction time of the reaction liquid B is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] In some optional embodiments, the concentration of maleic anhydride in toluene is 0.05-0.15 g / mL, for example, 0.05 g / mL, 0.06 g / mL, 0.07 g / mL, 0.08 g / mL, 0.09 g / mL, 0.10 g / mL, 0.11 g / mL, 0.12 g / mL, 0.13 g / mL, 0.14 g / mL or 0.15 g / mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In some optional embodiments, the mass ratio of maleic anhydride to ion coordination / intercalation modified montmorillonite is 0.05-0.1:1, for example, it can be 0.050:1, 0.055:1, 0.060:1, 0.065:1, 0.070:1, 0.075:1, 0.080:1, 0.085:1, 0.090:1, 0.095:1 or 0.100:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In some optional embodiments, the mass ratio of dicumyl peroxide to ion coordination / intercalation modified montmorillonite is 0.02-0.04:1, for example, it can be 0.020:1, 0.022:1, 0.024:1, 0.026:1, 0.028:1, 0.030:1, 0.032:1, 0.034:1, 0.036:1, 0.038:1 or 0.040:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] In some optional embodiments, the first temperature of the constant temperature reaction of the reaction liquid C is 100-120°C, for example, it can be 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] In some optional embodiments, the first time of the constant temperature reaction of the reaction liquid C is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In some optional embodiments, the second temperature of the constant temperature reaction of the reaction liquid C is 140-150°C, for example, it can be 140°C, 141°C, 142°C, 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, 149°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In some optional embodiments, the second time of the constant temperature reaction of the reaction liquid C is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] As a preferred technical solution of the present invention, in step S3, the mass ratio of maleic anhydride to metallocene polyethylene is 2-5:100, for example, it can be 2.0:100, 2.3:100, 2.6:100, 2.9:100, 3.2:100, 3.5:100, 3.8:100, 4.1:100, 4.4:100, 4.7:100 or 5.0:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In some optional embodiments, the mass ratio of diisopropyl peroxide to metallocene polyethylene is 0.2-0.4:100, for example, it can be 0.20:100, 0.22:100, 0.24:100, 0.26:100, 0.28:100, 0.30:100, 0.32:100, 0.34:100, 0.36:100, 0.38:100 or 0.40:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In some optional embodiments, the mass ratio of the antioxidant to the metallocene polyethylene is 0.1-0.2:100, for example, it can be 0.10:100, 0.11:100, 0.12:100, 0.13:100, 0.14:100, 0.15:100, 0.16:100, 0.17:100, 0.18:100, 0.19:100 or 0.20:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional embodiments, the temperature of the melt blending is 180-200°C, for example, it can be 180°C, 182°C, 184°C, 186°C, 188°C, 190°C, 192°C, 194°C, 196°C, 198°C or 200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional embodiments, the melt blending time is 5-10 min, for example, it can be 5.0 min, 5.5 min, 6.0 min, 6.5 min, 7.0 min, 7.5 min, 8.0 min, 8.5 min, 9.0 min, 9.5 min or 10.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional embodiments, the mass ratio of the glycidyl methacrylate to the preliminarily grafted metallocene polyethylene is 1-3:100, for example, it can be 1.0:100, 1.2:100, 1.4:100, 1.6:100, 1.8:100, 2.0:100, 2.2:100, 2.4:100, 2.6:100, 2.8:100 or 3.0:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional embodiments, the mass ratio of the ethyl acrylate to the preliminarily grafted metallocene polyethylene is 1-3:100, for example, it can be 1.0:100, 1.2:100, 1.4:100, 1.6:100, 1.8:100, 2.0:100, 2.2:100, 2.4:100, 2.6:100, 2.8:100 or 3.0:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional embodiments, the mass ratio of the magnesium chloride to the preliminarily grafted metallocene polyethylene is 0.5-1:100, for example, it can be 0.50:100, 0.55:100, 0.60:100, 0.65:100, 0.70:100, 0.75:100, 0.80:100, 0.85:100, 0.90:100, 0.95:100 or 1.00:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional embodiments, the mass ratio of the tributyl phosphate to the preliminarily grafted metallocene polyethylene is 0.5-1:100, for example, it can be 0.50:100, 0.55:100, 0.60:100, 0.65:100, 0.70:100, 0.75:100, 0.80:100, 0.85:100, 0.90:100, 0.95:100 or 1.00:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] As a preferred technical solution of the present invention, in step S4, the temperature of the twin-screw extruder is 200-210°C, for example, it can be 200°C, 201°C, 202°C, 203°C, 204°C, 205°C, 206°C, 207°C, 208°C, 209°C or 210°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional embodiments, the heat setting temperature is 80-100°C, for example, it can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional embodiments, the heat setting time is 20-40s, for example, it can be 20s, 22s, 24s, 26s, 28s, 30s, 32s, 34s, 36s, 38s or 40s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In a second aspect, the present invention provides a uniaxially stretched polyethylene composite film material. The uniaxially stretched polyethylene composite film material comprises polyethylene resin, polar group grafted nanosheet powder, modified polyethylene compatibilizer, antioxidant and lubricant, wherein the mass ratio of polyethylene resin, polar group grafted nanosheet powder, modified polyethylene compatibilizer, antioxidant and lubricant in the uniaxially stretched polyethylene composite film material is: (75-85): (5-10): (5-15): (0.2-0.3): (0.05-0.15).
[0039] In the present invention, montmorillonite is introduced as a nanosheet barrier, and its main function is to form a "maze effect" in the matrix material through its layered structure and high barrier performance, extending the diffusion path of gas or liquid molecules, thereby significantly improving the barrier performance of the material. Montmorillonite is a layered silicate mineral, and its crystal structure is composed of alternating stacking of silicon oxygen tetrahedron layers and aluminum oxygen octahedron layers to form a nanosheet structure with regular interlayer spacing. This structure gives montmorillonite a high specific surface area, high cation exchange capacity and good chemical stability. There are usually weak van der Waals forces and electrostatic effects between the layers of montmorillonite, and the interlayer cations can be replaced with other cations in the outside world through ion exchange, thereby providing a good basis for its functional modification.
[0040] In order to further improve the exfoliation and dispersibility of montmorillonite so that it can better exert its barrier properties in composite materials, the present invention performs ultrasonic treatment on montmorillonite. Ultrasonic treatment can induce cavitation effect, generate a large number of tiny bubbles in the liquid, and these bubbles will produce instantaneous local high temperature and high pressure environment during the process of formation and rupture. This high transient local pressure and temperature can destroy the van der Waals force and electrostatic action between montmorillonite layers, promote the exfoliation of montmorillonite layered structure, and form single-layer or multi-layer montmorillonite nanosheets. The exfoliated montmorillonite has a significantly increased specific surface area and more active sites, which can improve its interface effect with the polymer matrix, and provide active groups and reaction sites for subsequent chemical modification.
[0041] In order to further improve the compatibility and dispersion stability between montmorillonite and the polymer matrix, the present invention introduces 3-aminopropyltriethoxysilane to perform surface modification on the stripped montmorillonite. 3-aminopropyltriethoxysilane is a typical silane coupling agent, and its molecular structure contains triethoxysilane and amino groups. The triethoxysilane group can undergo condensation reaction with the surface of inorganic materials, and the amino group provides polar active sites for subsequent organic chemical modification. During the modification process, 3-aminopropyltriethoxysilane first undergoes a hydrolysis reaction to generate silanols, and the generated silanols then undergo a condensation reaction with the hydroxyl groups on the surface of the stripped montmorillonite, and the 3-aminopropyltriethoxysilane is fixed on the surface of the montmorillonite through a covalent bond.
[0042] This surface modification introduces amino functional groups, which significantly improves the surface activity and polarity of montmorillonite. On the one hand, the amino functional groups can further enhance the interaction between montmorillonite and the polymer matrix through hydrogen bonding or electrostatic interaction; on the other hand, the introduction of amino groups also provides active sites for subsequent organic chemical modifications (such as intercalation or grafting modification).
[0043] In addition, through the modification of 3-aminopropyltriethoxysilane, the interlayer environment of montmorillonite changes from hydrophilic to partially hydrophobic. This change in surface properties improves the dispersibility of montmorillonite in non-polar or weakly polar polymer matrices and effectively reduces the agglomeration of montmorillonite that may occur during the processing of composite materials. The modified montmorillonite not only has stronger interfacial adhesion ability, but can also be more evenly dispersed in the polyethylene matrix to form a stable nanocomposite structure, thereby greatly improving the barrier and mechanical properties of the material.
[0044] As a layered silicate mineral, montmorillonite is hydrophilic and has a small interlayer distance, which limits its interfacial compatibility and dispersibility with non-polar polymers to a certain extent. In the non-polar polymer matrix, unmodified montmorillonite tends to agglomerate and is difficult to disperse evenly, thus failing to fully exert the barrier properties and reinforcement effect of its nanosheet layer.
[0045] The present invention introduces N,N-dimethyloctadecyl ammonium chloride to perform intercalation modification on montmorillonite. N,N-dimethyloctadecyl ammonium chloride is a typical cationic surfactant, and its molecular structure contains an octadecyl long chain and a positively charged quaternary ammonium cation. During the intercalation modification process, the cation part thereof is inserted into the interlayer of montmorillonite through electrostatic action, and an ion exchange reaction occurs with the cations in the interlayer.
[0046] Through ion exchange, quaternary ammonium cations replace inorganic cations between montmorillonite layers and insert into the interlayer space. Due to the hydrophobicity of the octadecyl long chain, this intercalation modification significantly changes the interlayer environment of montmorillonite. First, the intercalation modification significantly widens the interlayer spacing of montmorillonite, making its layered structure looser, which provides a spatial basis for further intercalation and functionalization; second, the interlayer environment changes from hydrophilic to hydrophobic, greatly improving the compatibility and dispersibility of montmorillonite in the non-polar polyethylene matrix. In addition, more long-chain organic groups are exposed between the interlayers of intercalated montmorillonite, which can physically entangle or weakly interact with the polyethylene matrix, thereby further enhancing the interfacial bonding of the composite material.
[0047] Zinc oxide is an inorganic nanomaterial with excellent barrier properties, antibacterial properties and UV shielding capabilities, and its introduction provides additional functionality for modified montmorillonite. In the present invention, the functional modification of the interlayer space is further achieved by introducing zinc oxide into the interlayer of montmorillonite. Zinc oxide coordinates with the negative charge areas (partial negative charges from aluminum oxide octahedra or silicon oxide tetrahedra) of the interlayer of montmorillonite through its surface oxygen atoms to form a stable montmorillonite-zinc oxide composite structure. This coordination not only helps to stabilize the intercalation structure of montmorillonite, but also gives the modified montmorillonite material good barrier properties and antibacterial properties. In addition, zinc oxide may have a weak interaction with the inserted organic long-chain cations, which further improves the modification effect of montmorillonite. Through the synergistic modification of zinc oxide, the interlayer structure of montmorillonite is more stable, and the multifunctionality is significantly enhanced, which provides support for the barrier properties and additional functions (such as antibacterial and UV shielding) of the final composite material.
[0048] Maleic anhydride is a highly active bifunctional compound with an anhydride ring in its molecular structure. Its chemical properties enable it to react with various active groups on the surface of montmorillonite and the surface active points of zinc oxide. The anhydride group in maleic anhydride can undergo esterification reaction with the hydroxyl groups on the surface of montmorillonite to form a stable ester bond. This chemical bonding improves the polarity and activity of the montmorillonite surface and provides a stronger chemical basis for its interfacial bonding with the polyethylene matrix. Maleic anhydride can also react with the active points on the surface of zinc oxide to form a stable chemical bond, further enhancing the stability of the modified montmorillonite composite structure.
[0049] At the same time, the anhydride ring of maleic anhydride will undergo a ring-opening reaction to generate carboxyl and hydroxyl groups. These polar groups can significantly improve the compatibility of montmorillonite with the non-polar polyethylene matrix. On the one hand, the carboxyl and hydroxyl groups can form hydrogen bonds or weak chemical bonds with the polar groups in the polyethylene matrix; on the other hand, these polar groups can also form a microscopic interface network structure in the polyethylene matrix, which helps to improve the mechanical properties and barrier properties of the composite material.
[0050] In the present invention, metallocene polyethylene is introduced as one of the matrix materials. Metallocene polyethylene is a high-performance polyethylene synthesized by metallocene catalysts, and its greatest characteristics are its narrow molecular weight distribution and regular molecular chain structure. Compared with polyethylene synthesized by traditional Ziegler-Natta catalysts, metallocene polyethylene has higher crystallinity and more orderly arrangement of molecular chains, thereby showing excellent mechanical properties, thermal stability and chemical inertness. In addition, metallocene polyethylene has excellent processing properties and can meet the strict requirements for melt processing properties in film preparation. However, since metallocene polyethylene is a non-polar material, its molecular chain lacks polar groups and has poor interfacial compatibility with polar nanomaterials. This characteristic results in weak interfacial forces between metallocene polyethylene and polar components, and polar nanomaterials are prone to agglomeration in the matrix and cannot be evenly dispersed, thereby limiting the overall performance of the composite material.
[0051] In order to overcome this problem, the present invention functionalizes the metallocene polyethylene by chemical modification, aiming to introduce polar groups to improve its interfacial compatibility with polar components. Specifically, by grafting the metallocene polyethylene with maleic anhydride, polar anhydride groups are introduced into the molecular chain, thereby significantly improving its interfacial interaction with polar nanomaterials.
[0052] Under high temperature conditions, diisopropylbenzene peroxide decomposes to generate free radicals. These free radicals can extract hydrogen atoms from the molecular chain of metallocene polyethylene to generate polyethylene chain free radicals. The formed polyethylene chain free radicals have strong reactivity and are the core intermediates of the grafting reaction. Subsequently, the polyethylene chain free radicals react with the double bonds in the maleic anhydride molecules to graft the anhydride groups onto the polyethylene molecular chains. The anhydride group is a highly polar functional group. Its molecular structure contains two carbonyl groups that can form strong interfacial bonds with other polar components (such as hydroxyl or amino groups in modified montmorillonite) through hydrogen bonds, coordination or chemical bonds.
[0053] Through grafting modification, metallocene polyethylene is partially transformed from a highly non-polar material into a modified material with polar functions. The grafted anhydride group significantly improves the polarity of metallocene polyethylene, enabling it to form stronger interfacial forces with intercalation / ion coordination modified montmorillonite. At the same time, the grafting of maleic anhydride also improves the dispersion ability of the metallocene polyethylene matrix on montmorillonite, thereby effectively avoiding the agglomeration of nanosheets, improving the uniformity and interfacial bonding properties of the composite material, and enhancing the barrier properties and mechanical properties of the material.
[0054] In order to further optimize the polarity and interfacial properties of metallocene polyethylene, glycidyl methacrylate is also introduced as a synergistic modifier in the present invention. Glycidyl methacrylate is a bifunctional compound, which contains both epoxy groups and acrylate groups in the molecule. The epoxy group has high reactivity and can undergo a ring-opening addition reaction with polar groups (such as anhydride groups, hydroxyl groups or amino groups), while the acrylate group can undergo a copolymerization reaction with polyethylene chain free radicals under the initiation of free radicals. This enables glycidyl methacrylate to react chemically with metallocene polyethylene and polar components through a variety of reaction mechanisms.
[0055] Under the initiation of dicumyl peroxide, the acrylate group of glycidyl methacrylate can copolymerize with the free radical of the metallocene polyethylene chain, and glycidyl methacrylate is grafted onto the polyethylene molecular chain. The epoxy group in the grafted glycidyl methacrylate molecule can further undergo a ring-opening reaction with the anhydride group or hydroxyl group in the grafted maleic anhydride to generate more polar groups. Through the introduction of glycidyl methacrylate, polar functional groups such as ester groups and hydroxyl groups are simultaneously introduced into the modified metallocene polyethylene molecular chain. The hydroxyl group can form hydrogen bonds with the polar hydroxyl groups on the surface of montmorillonite, and the polar ester group can interact with the functional groups of montmorillonite or the surface active points of zinc oxide. These polar groups further enhance the interfacial interaction between metallocene polyethylene and modified montmorillonite. In addition, the introduction of glycidyl methacrylate also improves the processing performance and toughness of the modified polyethylene by forming a flexible molecular chain structure, making it have better fluidity and ductility during melt processing.
[0056] Through the synergistic grafting modification of maleic anhydride and glycidyl methacrylate, metallocene polyethylene is transformed from a non-polar material to a modified material with polar functions. By introducing polar groups such as anhydride, hydroxyl and ester groups, the polarity of metallocene polyethylene is significantly improved, enabling it to form a stronger interfacial bonding force with polar components such as modified montmorillonite and zinc oxide; secondly, the polar groups can form a stable chemical bond with the polar groups (such as hydroxyl, amino) in the modified montmorillonite or the surface active points of zinc oxide through hydrogen bonds, chemical bonds or coordination, thereby significantly improving the interfacial bonding properties of the composite material. The modified metallocene polyethylene can better disperse the montmorillonite flakes, avoid the agglomeration of montmorillonite in the non-polar polyethylene matrix, and thus form a uniformly distributed nanocomposite structure. The barrier properties, mechanical properties and processing properties of the composite material have been significantly improved, meeting the comprehensive performance requirements of high-performance packaging films.
[0057] Ethyl acrylate is a flexible monomer, and its molecular structure contains both an acrylate group and a flexible ethoxyalkyl chain. This structural characteristic makes ethyl acrylate not only have a certain polarity, but also can give the modified material better flexibility and processing performance through its flexible chain segment. Through the free radical-initiated grafting reaction, ethyl acrylate is grafted onto the molecular chain of metallocene polyethylene, and the flexible ethoxyalkyl chain is introduced into the grafted polyethylene molecular chain, while the polar ester group is retained. The flexible ethoxyalkyl chain of ethyl acrylate gives the modified metallocene polyethylene higher flexibility, making the material show better ductility and fluidity during processing. This flexible chain segment can play a "lubricating" role between polyethylene molecular chains, significantly reducing the cohesive force of the material, thereby improving the melt processing performance.
[0058] As a typical Lewis acid, magnesium chloride is used in the present invention to promote the grafting modification reaction. The characteristic of Lewis acid is that it can accept electron pairs and interact with polar groups in the material system, thereby regulating the reaction behavior at the interface. During the grafting process, magnesium chloride can coordinate with the anhydride group in maleic anhydride, reduce the electron density of the anhydride group, thereby increasing its activity of reacting with polyethylene chain free radicals. This effect promotes the grafting efficiency of maleic anhydride, so that more anhydride groups are successfully introduced into the metallocene polyethylene molecular chain. Secondly, magnesium chloride can also weakly coordinate with the epoxy group of glycidyl methacrylate, reduce the ring tension of the epoxy group, thereby promoting the ring opening reaction. After the ring opening, the glycidyl methacrylate can further react with the polar groups on the surface of maleic anhydride or montmorillonite to form a more stable interface bond.
[0059] The introduction of magnesium chloride not only improves the efficiency of the grafting reaction, but also enhances the polarity of the grafted modified metallocene polyethylene and improves its compatibility with montmorillonite. At the same time, magnesium chloride provides additional stability for the interfacial chemical bonding of the composite material by regulating the interfacial reaction behavior.
[0060] Tributyl phosphate is a commonly used plasticizer and dispersant, which can significantly reduce the viscosity of the material in the melt blending system, thereby improving the processing performance. In the present invention, the introduction of tributyl phosphate has the following effects: tributyl phosphate plays a lubricating role through its flexible molecular structure, reducing the cohesive force between the polyethylene molecular chains in the melt system. This effect can significantly reduce the viscosity during the melt blending process, thereby improving the fluidity and processing performance of the material; secondly, because tributyl phosphate has a certain polarity, it can interact weakly with the polar groups of the modified montmorillonite, thereby improving the dispersibility of montmorillonite in the polyethylene matrix. This effect can effectively avoid the agglomeration of montmorillonite in the matrix and ensure the uniform distribution of nanosheets in the composite material; in addition, as a plasticizer, tributyl phosphate can play a "lubricating" role between polyethylene molecular chains, giving the material higher flexibility and ductility.
[0061] Through the above modification, montmorillonite is evenly dispersed in the polyethylene matrix. The stripped montmorillonite is evenly distributed in the matrix in the form of single-layer or multi-layer nanosheets, and its layered structure forms a "maze effect" in the composite material. When gas molecules try to pass through the film, the nanosheets of montmorillonite will significantly extend the diffusion path of the gas molecules, thereby reducing the gas permeation rate and ultimately significantly improving the barrier properties of the composite material. At the same time, the interfacial bonding force between the polar groups (such as anhydride groups and hydroxyl groups) in the modified polyethylene matrix and montmorillonite is enhanced, making the dispersion of montmorillonite in the matrix more uniform, thereby further improving the overall performance of the nanocomposite material.
[0062] Uniaxial stretching is a key step in the formation of composite films, and plays a role in optimizing the microstructure of the material in the present invention: during the uniaxial stretching process, the polyethylene molecular chains are highly oriented along the stretching direction. This directional arrangement of the molecular chains not only improves the tensile strength of the film, but also optimizes the mechanical properties of the material; the uniaxial stretching process also promotes the orderly arrangement of montmorillonite nanosheets in the film. The directional arrangement of the montmorillonite flakes further enhances the "maze effect", making the diffusion path of gas molecules more tortuous, thereby significantly improving the barrier properties of the film. The stretched film is subjected to heat setting treatment to fix the oriented structure of the polyethylene molecular chains and the montmorillonite flakes to avoid relaxation and retraction of the molecular chains during the cooling process, resulting in a decrease in performance.
[0063] The present invention also has a synergistic enhancement effect. Maleic anhydride introduces polar anhydride groups on the metallocene polyethylene molecular chain through a grafting reaction. These anhydride groups not only significantly increase the polarity of polyethylene, but also generate carboxyl and hydroxyl groups through a ring-opening reaction, providing active sites for further interfacial reactions. The epoxy groups in the glycidyl methacrylate molecule can undergo a ring-opening reaction with the anhydride group or carboxyl group of maleic anhydride, thereby introducing more polar groups on the polyethylene molecular chain. The synergistic effect of maleic anhydride and glycidyl methacrylate increases the interfacial bonding force between the modified polyethylene and montmorillonite or other polar components by constructing a variety of polar groups on the polyethylene molecular chain. The flexible molecular structure of glycidyl methacrylate can also reduce the rigidity of polyethylene after grafting, alleviating the material brittleness problem caused by the introduction of rigid groups.
[0064] Ethyl acrylate introduces flexible ethoxyalkyl chains and polar ester groups into the polyethylene molecular chain through free radical grafting reaction. Maleic anhydride grafting provides anhydride groups and carboxyl groups, increasing the polarity of polyethylene. The flexible chain segments of ethyl acrylate alleviate the rigidity and processing difficulties caused by the introduction of polar groups in the polyethylene matrix after maleic anhydride grafting, thereby balancing the flexibility and strength of the material. The simultaneous presence of ester groups and carboxyl groups provides more binding sites for the interfacial interaction between polyethylene and modified montmorillonite, enhancing the interfacial bonding force.
[0065] After montmorillonite is modified by intercalation, the interlayer environment changes from hydrophilic to hydrophobic, and the interlayer spacing increases, providing more space for the polar groups of the modified polyethylene to interact with it. The anhydride groups, hydroxyl groups and ester groups introduced into the modified polyethylene by maleic anhydride, glycidyl methacrylate and ethyl acrylate can form a stable interface bond with the polar groups (such as hydroxyl groups and amino groups) on the surface of the modified montmorillonite through hydrogen bonds, van der Waals forces or chemical bonding. The intercalation structure of the modified montmorillonite and the polar groups of the modified polyethylene complement each other, ensuring the uniform dispersion of montmorillonite in the polyethylene matrix. This enhanced interfacial bonding force significantly improves the mechanical properties, barrier properties and thermal stability of the composite material.
[0066] The stripped montmorillonite is evenly distributed in the polyethylene matrix in the form of single-layer or multi-layer nanosheets. Its layered structure forms a "maze effect" in the material, extending the diffusion path of gas molecules. The polar groups in the modified polyethylene further promote the uniform distribution of montmorillonite in the matrix through interfacial bonding. The combination of the polar groups of the modified polyethylene and montmorillonite optimizes its dispersion and sheet orientation, ensuring the maximization of the "maze effect", thereby significantly improving the barrier properties of the film. The uniformity of montmorillonite dispersion also enhances the mechanical properties of the composite material, making it exhibit higher strength and toughness.
[0067] In a third aspect, the present invention provides an application of a uniaxially stretched polyethylene composite film material in the preparation of packaging materials.
[0068] Compared with the prior art, the present invention has the following beneficial effects: The present invention optimizes the dispersibility and interfacial compatibility of montmorillonite in a polyethylene matrix through multiple modification strategies, significantly improving the performance of the composite material. Ultrasonic exfoliation increases its specific surface area and active sites; 3-aminopropyltriethoxysilane modification introduces amino functional groups, improves surface polarity and changes the interlayer environment from hydrophilic to hydrophobic; N,N-dimethyloctadecylammonium chloride intercalation widens the interlayer spacing, enhances physical entanglement and interfacial bonding with polyethylene; zinc oxide introduction further stabilizes the intercalation structure and imparts antibacterial and ultraviolet shielding functions; maleic anhydride strengthens the interfacial bonding through chemical bonding. These synergistic effects make montmorillonite uniformly dispersed in the composite material, improving barrier properties, mechanical properties and functional characteristics.
[0069] The present invention functionalizes metallocene polyethylene by synergistic grafting of maleic anhydride and glycidyl methacrylate, introduces polar groups, significantly improves its interfacial compatibility and dispersibility with polar nanomaterials, and improves flexibility and processing performance. Combined with magnesium chloride to promote grafting efficiency and tributyl phosphate to improve dispersibility and fluidity, the modified metallocene polyethylene achieves uniform distribution of nanosheets, significantly enhances the barrier properties, mechanical properties and processing properties of the composite material, and meets the application requirements of high-performance films. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is a flow chart of the method for preparing the uniaxially stretched polyethylene composite film material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0071] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications made to the embodiments recorded herein.
[0072] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products without further purification or treatment.
[0073] Example 1
[0074] This embodiment provides a uniaxially stretched polyethylene composite film material and a preparation method thereof, wherein the preparation method specifically comprises the following steps: S1: ultrasonically treating a montmorillonite dispersion to obtain an exfoliated montmorillonite dispersion, and adding 3-aminopropyltriethoxysilane to obtain a pretreated montmorillonite; Specifically, S1: a montmorillonite dispersion with a mass fraction of 8 wt.% is subjected to ultrasonic treatment at a power of 200 W for 30 min to obtain an exfoliated montmorillonite dispersion, 3-aminopropyltriethoxysilane is added at a mass ratio of 0.04:1 to montmorillonite to obtain a reaction solution A, and the reaction is stirred at 78° C. for 2 h, followed by centrifugation, washing, and drying to obtain a pretreated montmorillonite; S2: reacting the pretreated montmorillonite with N,N-dimethyloctadecylammonium chloride and zinc oxide to obtain ion coordination / intercalation modified montmorillonite; reacting the pretreated montmorillonite with maleic anhydride and diisopropylbenzene peroxide in toluene to obtain polar group grafted nanosheet powder; Specifically, S2: N, N-dimethyloctadecyl ammonium chloride in a mass ratio of 0.04:1 to the pretreated montmorillonite dispersion with a mass fraction of 2wt.% and zinc oxide in a mass ratio of 0.03:1 to the pretreated montmorillonite are added to obtain a reaction solution B, which is stirred at 70°C for 1 hour and then spray-dried to obtain an ion-coordinated / intercalated modified montmorillonite; maleic anhydride is dispersed in toluene, wherein the concentration of maleic anhydride in toluene is 0.1g / mL, and the mass ratio of maleic anhydride to the ion-coordinated / intercalated modified montmorillonite is 0.08:1, diisopropylbenzene peroxide in a mass ratio of 0.03:1 to the ion-coordinated / intercalated modified montmorillonite is added to obtain a grafting solution, and the ion-coordinated / intercalated modified montmorillonite is added under an inert atmosphere to obtain a reaction solution C, which is reacted at a constant temperature of 100°C for 1 hour, then heated to 145°C and reacted for 1 hour, and rotary evaporated to obtain a polar group-grafted nanosheet powder; S3: melt-blending metallocene polyethylene with maleic anhydride, dicumyl peroxide and antioxidant to obtain a preliminarily grafted metallocene polyethylene; blending the preliminarily grafted metallocene polyethylene with glycidyl methacrylate, ethyl acrylate, magnesium chloride and tributyl phosphate to obtain a modified polyethylene compatibilizer; Specifically, S3: melt-blending metallocene polyethylene with maleic anhydride, diisopropyl peroxide, and antioxidant 1010 at 180° C. for 5 minutes, and extruding to obtain a preliminarily grafted metallocene polyethylene, wherein the mass ratio of maleic anhydride to metallocene polyethylene is 3:100, the mass ratio of diisopropyl peroxide to metallocene polyethylene is 0.35:100, and the mass ratio of antioxidant 1010 to metallocene polyethylene is 0.15:100; blending it with glycidyl methacrylate, ethyl acrylate, magnesium chloride, and tributyl phosphate to obtain a modified polyethylene compatibilizer, wherein the mass ratio of glycidyl methacrylate to the preliminarily grafted metallocene polyethylene is 2:100, the mass ratio of ethyl acrylate to the preliminarily grafted metallocene polyethylene is 1.8:100, the mass ratio of magnesium chloride to the preliminarily grafted metallocene polyethylene is 0.8:100, and the mass ratio of tributyl phosphate to the preliminarily grafted metallocene polyethylene is 0.7:100; S4: The polyethylene resin, the polar group-grafted nanosheet powder, the modified polyethylene compatibilizer and the additive are melt-processed and treated to obtain a uniaxially stretched polyethylene composite film material.
[0075] Specifically, S4: the polyethylene resin is mixed evenly with the nanosheet powder grafted with polar groups, the modified polyethylene compatibilizer and antioxidant 1010, and the lubricant zinc stearate, and then put into a twin-screw extruder to extrude and cast into a sheet at 200°C, which is uniaxially stretched, heat-set at 80°C for 20s, and then cooled to obtain a uniaxially stretched polyethylene composite film material, wherein the mass ratio of the polyethylene resin to the nanosheet powder grafted with polar groups, the modified polyethylene compatibilizer and antioxidant 1010, and the lubricant zinc stearate is 80:8:10:0.25:0.1.
[0076] Example 2
[0077] This embodiment provides a uniaxially stretched polyethylene composite film material and a preparation method thereof, wherein the preparation method specifically comprises the following steps: S1: ultrasonically treating a montmorillonite dispersion to obtain an exfoliated montmorillonite dispersion, and adding 3-aminopropyltriethoxysilane to obtain a pretreated montmorillonite; Specifically, S1: a montmorillonite dispersion with a mass fraction of 5 wt.% was subjected to ultrasonic treatment at a power of 270 W for 50 min to obtain an exfoliated montmorillonite dispersion, 3-aminopropyltriethoxysilane was added at a mass ratio of 0.045:1 to montmorillonite to obtain a reaction solution A, and the reaction was stirred at 75° C. for 2.5 h, followed by centrifugation, washing, and drying to obtain a pretreated montmorillonite; S2: reacting the pretreated montmorillonite with N,N-dimethyloctadecylammonium chloride and zinc oxide to obtain ion coordination / intercalation modified montmorillonite; reacting the pretreated montmorillonite with maleic anhydride and diisopropylbenzene peroxide in toluene to obtain polar group grafted nanosheet powder; Specifically, S2: N, N-dimethyloctadecyl ammonium chloride and zinc oxide in a mass ratio of 0.02:1 to the pretreated montmorillonite dispersion with a mass fraction of 3 wt.% were added to obtain a reaction solution B, which was stirred for reaction at 80°C for 1.2 h and then spray-dried to obtain ion coordination / intercalation modified montmorillonite; maleic anhydride was dispersed in toluene, wherein the concentration of maleic anhydride in toluene was 0.05 g / mL, the mass ratio of maleic anhydride to ion coordination / intercalation modified montmorillonite is 0.1:1, dicumyl peroxide is added in a mass ratio of 0.02:1 to ion coordination / intercalation modified montmorillonite to obtain a grafting solution, and ion coordination / intercalation modified montmorillonite is added under an inert atmosphere to obtain a reaction solution C, and the reaction is carried out at a constant temperature of 110° C. for 1.5 h, then the temperature is increased to 140° C. and the reaction is carried out for 1.6 h, and a polar group-grafted nanosheet powder is obtained by rotary evaporation; S3: melt-blending metallocene polyethylene with maleic anhydride, dicumyl peroxide and antioxidant to obtain a preliminarily grafted metallocene polyethylene; blending the preliminarily grafted metallocene polyethylene with glycidyl methacrylate, ethyl acrylate, magnesium chloride and tributyl phosphate to obtain a modified polyethylene compatibilizer; Specifically, S3: melt-blending metallocene polyethylene with maleic anhydride, diisopropylbenzene peroxide, and antioxidant 1076 at 190°C for 8 minutes, and extruding to obtain a preliminarily grafted metallocene polyethylene, wherein the mass ratio of maleic anhydride to metallocene polyethylene is 2:100, the mass ratio of diisopropylbenzene peroxide to metallocene polyethylene is 0.2:100, and the mass ratio of antioxidant 1076 to metallocene polyethylene is 0.17:100; blending it with glycidyl methacrylate, ethyl acrylate, magnesium chloride, and tributyl phosphate to obtain a modified polyethylene compatibilizer, wherein the mass ratio of glycidyl methacrylate to the preliminarily grafted metallocene polyethylene is 1:100, the mass ratio of ethyl acrylate to the preliminarily grafted metallocene polyethylene is 3:100, the mass ratio of magnesium chloride to the preliminarily grafted metallocene polyethylene is 1:100, and the mass ratio of tributyl phosphate to the preliminarily grafted metallocene polyethylene is 0.6:100; S4: The polyethylene resin, the polar group-grafted nanosheet powder, the modified polyethylene compatibilizer and the additive are melt-processed and treated to obtain a uniaxially stretched polyethylene composite film material.
[0078] Specifically, S4: the polyethylene resin is mixed evenly with the nanosheet powder grafted with polar groups, the modified polyethylene compatibilizer and antioxidant 1076, and the lubricant calcium stearate, and then put into a twin-screw extruder to extrude and cast into a sheet at 208°C, which is uniaxially stretched, heat-set at 90°C for 30s, and then cooled to obtain a uniaxially stretched polyethylene composite film material, wherein the mass ratio of the polyethylene resin to the nanosheet powder grafted with polar groups, the modified polyethylene compatibilizer and antioxidant 1076, and the lubricant calcium stearate is 82:5:5:0.2:0.12.
[0079] Example 3
[0080] This embodiment provides a uniaxially stretched polyethylene composite film material and a preparation method thereof, wherein the preparation method specifically comprises the following steps: S1: ultrasonically treating a montmorillonite dispersion to obtain an exfoliated montmorillonite dispersion, and adding 3-aminopropyltriethoxysilane to obtain a pretreated montmorillonite; Specifically, S1: a montmorillonite dispersion with a mass fraction of 7 wt.% was subjected to ultrasonic treatment at a power of 240 W for 40 min to obtain an exfoliated montmorillonite dispersion, 3-aminopropyltriethoxysilane was added at a mass ratio of 0.03:1 to montmorillonite to obtain a reaction solution A, and the reaction was stirred at 70° C. for 2.7 h, followed by centrifugation, washing, and drying to obtain a pretreated montmorillonite; S2: reacting the pretreated montmorillonite with N,N-dimethyloctadecylammonium chloride and zinc oxide to obtain ion coordination / intercalation modified montmorillonite; reacting the pretreated montmorillonite with maleic anhydride and diisopropylbenzene peroxide in toluene to obtain polar group grafted nanosheet powder; Specifically, S2: N,N-dimethyloctadecylammonium chloride in a mass ratio of 0.03:1 to the pretreated montmorillonite dispersion with a mass fraction of 3.5wt.% and zinc oxide in a mass ratio of 0.01:1 to the pretreated montmorillonite were added to obtain a reaction solution B, which was stirred at 78°C for 1.6h and then spray-dried to obtain an ion-coordinated / intercalated modified montmorillonite; maleic anhydride was dispersed in toluene, wherein the concentration of maleic anhydride in toluene was 0.12 g / mL, the mass ratio of maleic anhydride to ion coordination / intercalation modified montmorillonite is 0.05:1, dicumyl peroxide is added in a mass ratio of 0.035:1 to ion coordination / intercalation modified montmorillonite to obtain a grafting solution, and ion coordination / intercalation modified montmorillonite is added under an inert atmosphere to obtain a reaction solution C, and the reaction is carried out at a constant temperature of 115°C for 1.8 hours, then the temperature is increased to 147°C and the reaction is carried out for 1.4 hours, and a polar group-grafted nanosheet powder is obtained by rotary evaporation; S3: melt-blending metallocene polyethylene with maleic anhydride, dicumyl peroxide and antioxidant to obtain a preliminarily grafted metallocene polyethylene; blending the preliminarily grafted metallocene polyethylene with glycidyl methacrylate, ethyl acrylate, magnesium chloride and tributyl phosphate to obtain a modified polyethylene compatibilizer; Specifically, S3: melt-blending metallocene polyethylene with maleic anhydride, diisopropylbenzene peroxide, and antioxidant 1010 at 195° C. for 7 minutes, and extruding to obtain a preliminarily grafted metallocene polyethylene, wherein the mass ratio of maleic anhydride to metallocene polyethylene is 4:100, the mass ratio of diisopropylbenzene peroxide to metallocene polyethylene is 0.38:100, and the mass ratio of antioxidant 1010 to metallocene polyethylene is 0.1:100; blending it with glycidyl methacrylate, ethyl acrylate, magnesium chloride, and tributyl phosphate to obtain a modified polyethylene compatibilizer, wherein the mass ratio of glycidyl methacrylate to the preliminarily grafted metallocene polyethylene is 2.5:100, the mass ratio of ethyl acrylate to the preliminarily grafted metallocene polyethylene is 2:100, the mass ratio of magnesium chloride to the preliminarily grafted metallocene polyethylene is 0.5:100, and the mass ratio of tributyl phosphate to the preliminarily grafted metallocene polyethylene is 1:100; S4: The polyethylene resin, the polar group-grafted nanosheet powder, the modified polyethylene compatibilizer and the additive are melt-processed and treated to obtain a uniaxially stretched polyethylene composite film material.
[0081] Specifically, S4: the polyethylene resin is mixed evenly with the nanosheet powder grafted with polar groups, the modified polyethylene compatibilizer and antioxidant 1010, and the lubricant calcium stearate, and then put into a twin-screw extruder to extrude and cast into a sheet at 204°C, which is uniaxially stretched, heat-set at 95°C for 35 seconds, and then cooled to obtain a uniaxially stretched polyethylene composite film material, wherein the mass ratio of the polyethylene resin to the nanosheet powder grafted with polar groups, the modified polyethylene compatibilizer and antioxidant 1010, and the lubricant calcium stearate is 75:7:12:0.28:0.05.
[0082] Example 4
[0083] This embodiment provides a uniaxially stretched polyethylene composite film material and a preparation method thereof, wherein the preparation method specifically comprises the following steps: S1: ultrasonically treating a montmorillonite dispersion to obtain an exfoliated montmorillonite dispersion, and adding 3-aminopropyltriethoxysilane to obtain a pretreated montmorillonite; Specifically, S1: a montmorillonite dispersion with a mass fraction of 10 wt.% is subjected to ultrasonic treatment at a power of 300 W for 60 min to obtain an exfoliated montmorillonite dispersion, 3-aminopropyltriethoxysilane is added at a mass ratio of 0.05:1 to montmorillonite to obtain a reaction solution A, and the reaction is stirred at 80° C. for 3 h, followed by centrifugation, washing, and drying to obtain a pretreated montmorillonite; S2: reacting the pretreated montmorillonite with N,N-dimethyloctadecylammonium chloride and zinc oxide to obtain ion coordination / intercalation modified montmorillonite; reacting the pretreated montmorillonite with maleic anhydride and diisopropylbenzene peroxide in toluene to obtain polar group grafted nanosheet powder; Specifically, S2: N, N-dimethyloctadecyl ammonium chloride in a mass ratio of 0.05:1 to the pretreated montmorillonite dispersion with a mass fraction of 4 wt.% and zinc oxide in a mass ratio of 0.023:1 to the pretreated montmorillonite were added to obtain a reaction solution B, which was stirred for reaction at 75°C for 2 hours and then spray-dried to obtain an ion-coordinated / intercalated modified montmorillonite; maleic anhydride was dispersed in toluene, wherein the concentration of maleic anhydride in toluene was The mass ratio of maleic anhydride to ion coordination / intercalation modified montmorillonite is 0.15 g / mL, the mass ratio of maleic anhydride to ion coordination / intercalation modified montmorillonite is 0.07:1, dicumyl peroxide is added in a mass ratio of 0.04:1 to ion coordination / intercalation modified montmorillonite to obtain a grafting solution, and ion coordination / intercalation modified montmorillonite is added under an inert atmosphere to obtain a reaction solution C, and the reaction is carried out at a constant temperature of 120° C. for 2 h, then the temperature is raised to 150° C. and the reaction is carried out for 2 h, and a polar group-grafted nanosheet powder is obtained by rotary evaporation; S3: melt-blending metallocene polyethylene with maleic anhydride, dicumyl peroxide and antioxidant to obtain a preliminarily grafted metallocene polyethylene; blending the preliminarily grafted metallocene polyethylene with glycidyl methacrylate, ethyl acrylate, magnesium chloride and tributyl phosphate to obtain a modified polyethylene compatibilizer; Specifically, S3: melt-blending metallocene polyethylene with maleic anhydride, diisopropylbenzene peroxide, and antioxidant 1076 at 200°C for 10 minutes, and extruding to obtain a preliminarily grafted metallocene polyethylene, wherein the mass ratio of maleic anhydride to metallocene polyethylene is 5:100, the mass ratio of diisopropylbenzene peroxide to metallocene polyethylene is 0.4:100, and the mass ratio of antioxidant 1076 to metallocene polyethylene is 0.2:100; blending it with glycidyl methacrylate, ethyl acrylate, magnesium chloride, and tributyl phosphate to obtain a modified polyethylene compatibilizer, wherein the mass ratio of glycidyl methacrylate to the preliminarily grafted metallocene polyethylene is 3:100, the mass ratio of ethyl acrylate to the preliminarily grafted metallocene polyethylene is 2.5:100, the mass ratio of magnesium chloride to the preliminarily grafted metallocene polyethylene is 0.7:100, and the mass ratio of tributyl phosphate to the preliminarily grafted metallocene polyethylene is 0.5:100; S4: The polyethylene resin, the polar group-grafted nanosheet powder, the modified polyethylene compatibilizer and the additive are melt-processed and treated to obtain a uniaxially stretched polyethylene composite film material.
[0084] Specifically, S4: the polyethylene resin is mixed evenly with the nanosheet powder grafted with polar groups, the modified polyethylene compatibilizer and antioxidant 1076, and the lubricant zinc stearate, and then put into a twin-screw extruder to extrude and cast into a sheet at 210°C, which is uniaxially stretched, heat-set at 100°C for 40s, and then cooled to obtain a uniaxially stretched polyethylene composite film material, wherein the mass ratio of the polyethylene resin to the nanosheet powder grafted with polar groups, the modified polyethylene compatibilizer and antioxidant 1076, and the lubricant zinc stearate is 85:10:15:0.3:0.15.
[0085] Comparative Example 1 This comparative example provides a uniaxially stretched polyethylene composite film material, which differs from Example 1 in that, in S2, the mass ratio of N,N-dimethyloctadecylammonium chloride to pretreated montmorillonite is 0.1:1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0086] Comparative Example 2 This comparative example provides a uniaxially stretched polyethylene composite film material, which differs from Example 1 in that, in S2, the mass ratio of N,N-dimethyloctadecylammonium chloride to pretreated montmorillonite is 0.01:1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0087] Comparative Example 3 This comparative example provides a uniaxially stretched polyethylene composite film material, which differs from Example 1 in that, in S2, the mass ratio of maleic anhydride to ion coordination / intercalation modified montmorillonite is 0.2:1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0088] Comparative Example 4 This comparative example provides a uniaxially stretched polyethylene composite film material, which differs from Example 1 in that, in S2, the mass ratio of maleic anhydride to ion coordination / intercalation modified montmorillonite is 0.01:1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0089] Comparative Example 5 This comparative example provides a uniaxially stretched polyethylene composite film material, which differs from Example 1 in that, in S4, the mass ratio of the polyethylene resin to the nanosheet powder grafted with polar groups, the modified polyethylene compatibilizer and antioxidant 1010, and the lubricant zinc stearate is 80:8:20:0.25:0.1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0090] Comparative Example 6 This comparative example provides a uniaxially stretched polyethylene composite film material, which differs from Example 1 in that, in S4, the mass ratio of the polyethylene resin to the polar group grafted nanosheet powder, the modified polyethylene compatibilizer and antioxidant 1010, and the lubricant zinc stearate is 80:8:2:0.25:0.1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0091] The performance test of the uniaxially stretched polyethylene composite film materials of the above-mentioned Examples 1-4 and Comparative Examples 1-6 was carried out, and the specific process is as follows: Test the water vapor transmission rate of samples according to GB / T1037-2021; Carry out oxygen transmission rate test on samples according to GB / T1038.1-2022; The tensile strength of the samples was tested using a universal tensile testing machine; The test results are shown in Table 1.
[0092] Table 1: Test results of uniaxially stretched polyethylene composite film materials of Examples 1-4 and Comparative Examples 1-6
[0093] From the test results of Example 1 and Comparative Examples 1 and 2, it can be seen that when the mass ratio of N,N-dimethyloctadecylammonium chloride to pretreated montmorillonite is too high, the excess organic modifier accumulates between the layers to form a continuous phase, destroying the layered structure of montmorillonite, resulting in an increase in water vapor transmission rate to 3.42. At the same time, due to the unstable interlayer structure, the gas diffusion channels increase, making the oxygen permeability increase to 2.84 , the tensile strength of the material also dropped to 38.6MPa; when its mass ratio was too low, the modification effect was insufficient, resulting in poor dispersion of montmorillonite and the formation of agglomeration areas. Although the water vapor permeability was 2.68 However, due to the increase in interface defects, the oxygen transmission rate increased to 2.23 , the tensile strength also dropped to 42.3MPa; From the test results of Example 1 and Comparative Examples 3 and 4, it can be seen that when the mass ratio of maleic anhydride to ion coordination / intercalation modified montmorillonite is too high, the excess maleic anhydride undergoes self-crosslinking reaction and is enriched at the interface, resulting in a water vapor transmission rate increase to 3.15. ; At the same time, due to the damage of the interlayer structure, the oxygen permeability increased to 2.45 , excessive cross-linking leads to embrittlement of the material, and the tensile strength drops to 35.8MPa; when its mass ratio is too low, insufficient grafting degree affects the interfacial compatibility, although the water vapor permeability is 2.48 , but insufficient interface bonding caused the oxygen permeability to rise to 2.12 , the tensile strength also dropped to 41.5MPa; From the test results of Example 1 and Comparative Examples 5 and 6, it can be seen that when the amount of modified polyethylene compatibilizer added is too high, the excess compatibilizer reduces the crystallinity of the matrix, resulting in the water vapor transmission rate increasing to 3.25. ; At the same time, due to the increase of amorphous area, the oxygen permeability increased to 2.38 , the tensile strength of the material also dropped to 39.2MPa; when the addition amount was too low, the lack of compatibility led to uneven dispersion, although the water vapor permeability was 2.85 , but insufficient interface bonding causes the oxygen permeability to rise to 2.32 , the tensile strength also dropped to 36.8MPa.
[0094] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a uniaxially stretched polyethylene composite film material, characterized in that: The preparation method comprises: S1: ultrasonically treating a montmorillonite dispersion to obtain an exfoliated montmorillonite dispersion, and adding 3-aminopropyltriethoxysilane to obtain a pretreated montmorillonite; S2: reacting the pretreated montmorillonite with N,N-dimethyloctadecylammonium chloride and zinc oxide to obtain ion coordination / intercalation modified montmorillonite; reacting the pretreated montmorillonite with maleic anhydride and diisopropylbenzene peroxide in toluene to obtain polar group grafted nanosheet powder; S3: melt-blending metallocene polyethylene with maleic anhydride, dicumyl peroxide and antioxidant to obtain a preliminarily grafted metallocene polyethylene; blending the preliminarily grafted metallocene polyethylene with glycidyl methacrylate, ethyl acrylate, magnesium chloride and tributyl phosphate to obtain a modified polyethylene compatibilizer; S4: The polyethylene resin, the polar group-grafted nanosheet powder, the modified polyethylene compatibilizer and the additive are melt-processed and treated to obtain a uniaxially stretched polyethylene composite film material.
2. The method for preparing a uniaxially stretched polyethylene composite film material according to claim 1, characterized in that: In S1: the mass ratio of the 3-aminopropyltriethoxysilane to montmorillonite is 0.03-0.05:
1.
3. The method for preparing a uniaxially stretched polyethylene composite film material according to claim 1, characterized in that: In S2: The mass ratio of the N,N-dimethyloctadecylammonium chloride to the pretreated montmorillonite is 0.02-0.05:1; The mass ratio of the zinc oxide to the pretreated montmorillonite is 0.01-0.03:
1.
4. The method for preparing a uniaxially stretched polyethylene composite film material according to claim 1, characterized in that: In S2: The mass ratio of maleic anhydride to ion coordination / intercalation modified montmorillonite is 0.05-0.1:1; The mass ratio of the dicumyl peroxide to the ion coordination / intercalation modified montmorillonite is 0.02-0.04:
1.
5. The method for preparing a uniaxially stretched polyethylene composite film material according to claim 1, characterized in that: In S3: The mass ratio of maleic anhydride to metallocene polyethylene is 2-5:100; The mass ratio of the dicumyl peroxide to the metallocene polyethylene is 0.2-0.4:
100.
6. The method for preparing a uniaxially stretched polyethylene composite film material according to claim 1, characterized in that: In S3: The antioxidant is antioxidant 1010 or antioxidant 1076; The mass ratio of the antioxidant to the metallocene polyethylene is 0.1-0.2:
100.
7. The method for preparing a uniaxially stretched polyethylene composite film material according to claim 1, characterized in that: In S3: The mass ratio of the glycidyl methacrylate to the preliminarily grafted metallocene polyethylene is 1-3:100; The mass ratio of the ethyl acrylate to the preliminarily grafted metallocene polyethylene is 1-3:100; The mass ratio of the magnesium chloride to the preliminarily grafted metallocene polyethylene is 0.5-1:100; The mass ratio of the tributyl phosphate to the preliminarily grafted metallocene polyethylene is 0.5-1:
100.
8. The method for preparing a uniaxially stretched polyethylene composite film material according to claim 1, characterized in that: In S4: The auxiliary agents are antioxidants and lubricants; The lubricant is zinc stearate or calcium stearate.
9. A uniaxially stretched polyethylene composite film material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The mass ratio of polyethylene resin, polar group-grafted nanosheet powder, modified polyethylene compatibilizer, antioxidant and lubricant in the uniaxially stretched polyethylene composite film material is: (75-85): (5-10): (5-15): (0.2-0.3): (0.05-0.15).
10. Use of a uniaxially stretched polyethylene composite film material prepared by the preparation method according to any one of claims 1 to 8 in preparing packaging materials.
Citation Information
Patent Citations
High-barrier puncture-resistant polyethylene composite film as well as preparation method and application thereof
CN118700596A
Preparation method of high-strength polyethylene blown film
CN119060444A
Triple ethylene-propylene rubber / montmorillonoid peeling nano composite material and its preparing method
CN1425712A
Polyethylene Composite for High-Pressure Pipes
KR1020040089206A
manufacturing method of polyethylene compositematerials containing lipophilic nano-clay
KR1020050030818A
Cited By
Multifunctional high-barrier multilayer packaging film and preparation method thereof
CN121590108A
A multifunctional high-barrier multilayer packaging film and its preparation method
CN121590108B